THE IMPACT OF PLAY ACTIVITY ON THE COGNITIVE AND SOCIO-Emotional Development of Preschool Children (Universal International Scientific Journal, 2026)
The article highlights the pedagogical conditions and opportunities for the cognitive and socio-emotional development of preschool children through play activities, and substantiates the content and essence of cognitive and socio-emotional development.
Keywords: play, talent, social development, emotional development, cognitive development, thinking, speech, emotional stability, reading ability, learning through play, the child's personality, imagination, thinking, memory.